Fillet weld strength analysis for cantilever loading: an investigation of single-sided fillet weld strength in bending applications - McPheron, Tyler J.; M. Stwalley III, Robert (Politeknik Negeri Lhokseumawe, 2024)
Theoretical calculations for assessing the strength of a welded connection in design rely on two parameters: the tensile strength of the weld filler metal and the effective area. It is important to note that the type of load applied can significantly affect the theoretical strength of the weld. According to the AWS Structural Welding Code D1.1, when the load is applied parallel to the weld in a welded member, a reduction of 70% is recommended. This remaining factor of 0.30 has been determined through well-accepted tests to provide factors of safety between 2.2 for shearing forces parallel to the longitudinal axis of the weld and 4.6 for forces normal to the axis under service loading. When a load is applied perpendicular to the weld in a welded member, the entire value of the tensile strength of the weld filler metal is used to calculate the strength. However, there are no similar considerations for a load applied in a bending configuration. While it is not recommended for structural design, fillet welded members can experience loading that causes material deflection, resulting in a bending scenario. This is particularly relevant in repairs. The configuration of a cantilevered beam creates a different loading scenario with additional stresses on the weld, which differ from those of a perpendicular or parallel load. This research experiment was conducted to initially understand and analyze the strength of a GMAW weld under cantilevered bending and to derive a mathematical equation that provides a factor of safety in the range of 2.2-4.6, similar to the previous findings.